Teaching programming skills to finance students: how to design and teach a great course - Yuxing Yan (Financial Innovation, 2017)
A motivated finance-major student should master at least one programming language. This is especially true for students from quantitative finance, business analytics, those attending a Master of Science in Finance or other financial engineering programs. Among the preferred languages, R holds one of the first places. This paper explains seven critical factors for designing and teaching a programming course: strong motivation, a good textbook, hands-on learning environment, being data intensive, a challenging term project, multiple supporting R datasets, and an easy way to upload such R datasets.
Keywords: A2; I22; G00; 650; Programming skills; Quantitative-finance; Financial engineering; R; Open-source finance; Data analytics